2015
DOI: 10.1371/journal.pone.0123706
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Carbapenem-Resistant Gram Negatives in Italian Transplant Recipients: A Nationwide Surveillance Study

Abstract: BackgroundBacterial infections remain a challenge to solid organ transplantation. Due to the alarming spread of carbapenem-resistant gram negative bacteria, these organisms have been frequently recognized as cause of severe infections in solid organ transplant recipients.Methods and FindingsBetween 15 May and 30 September 2012 we enrolled 887 solid organ transplant recipients in Italy with the aim to describe the epidemiology of gram negative bacteria spreading, to explore potential risk factors and to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 17 publications
3
54
0
1
Order By: Relevance
“…4,18 For example, a nationwide surveillance study of carbapenem-resistant Gram negative infections in Italian SOT recipients showed that CRE comprised 15.7% of Gram negative infections, with Klebsiella spp comprising 49% of carbapenem-resistant isolates. 19 The incidence of post-SOT CRKP infection varies considerably by center and type of transplant (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In general, CRKP infections occur early after transplant, with most studies reporting a median time of <50 days from transplant to infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,18 For example, a nationwide surveillance study of carbapenem-resistant Gram negative infections in Italian SOT recipients showed that CRE comprised 15.7% of Gram negative infections, with Klebsiella spp comprising 49% of carbapenem-resistant isolates. 19 The incidence of post-SOT CRKP infection varies considerably by center and type of transplant (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In general, CRKP infections occur early after transplant, with most studies reporting a median time of <50 days from transplant to infection.…”
mentioning
confidence: 99%
“…Reported mortality rates among SOT recipients with CRE infection generally range from 30-50%, and post-transplant CRKP infections have been associated with as much as a 10-fold risk of death. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, a more recent cohort of 164 SOT recipients across 15 international sites confirmed that while CRE infection typically occurs in the early post-transplant period, the one-year survival rate of patients who developed CRE infection within the first year of transplant was 72%. 34 While CRKP infections remain the most common type of CRE infection in SOT recipients, infections due to carbapenem-resistant Enterobacter spp., as well as NDM-and OXA-48-producing K. pneumoniae have also been reported.…”
mentioning
confidence: 99%
“…In addition to these studies on XDR A baumannii, several other studies investigated carbapenem resistance in A baumannii and found it was quite common. 8,15,20,27,28 Carbapenem resistance in A baumannii in these studies ranged from 15.3% from Reddy and colleagues 27 to 75% from De Gouvea and colleagues. 8,15 Six studies investigated Pseudomonas aeruginosa.…”
Section: Prevalence Of Pathogens In Solid Organ Transplantmentioning
confidence: 73%
“…It is worth noting that the resistance rate in isolates of Klebsiella species has been shown to be 49.1%; the difference may be because most of the isolates were isolated among recipients of hearts and lungs. 6 In addition to gram-negative bacteria resistance to cephalosporins and carbapenems, controlling gram-positive strains resistant to the spread of betalactam antibiotics (which are resistant to penicillinase, such as oxacillin and glycopeptide-like vancomycin), including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE) isolates, are of special importance. In addition to development of resistance to these antibiotics, colonization in patients before and after transplant plays a major role in incidence of infection after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, resistance in gram-negative bacteria mostly occurs through extended-spectrum beta-lactamases (ESBLs) and carbapenemase enzymes. 4,6 In gram-positive bacteria, resistance occurs through penicillinase 7 and genes that cause resistance to vancomycin. 7,8 Therefore, the aim of this study was to evaluate the prevalence of bacterial infections, their types, and the antibiotic resistance rate in kidney recipients.…”
Section: Introductionmentioning
confidence: 99%